Methods For an Acceptable Traffic Noise Level Design - Sviben, Zlatko; Toš, Zdravko; Borković, Miroslav (Promet - Traffic&Transportation, 2004)
Road noise disturbance on rough roads by means of loudnesssensor caused by wideband signal components with a significantimpact of tonal effects on smooth roads and in specificactions in driving lead to the annoyance of drivers. A systemicapproach has been applied for the sound quality estimation ofphysical properties of various noise sources and structuralvibroacoustic car properties and its components as an integratedparameter in car design for the purpose of the developmentand vehicle noise reduction. Simulation of the most importantcharacteristics of listening impressions was performedby modem systems of signal analysis together with the presentationof loudness, sharpness, and roughness as essential quantities.Optimization of the noise control measuring regarding vehiclesound was obtained by means of a simulation system withthe capability of the real time original sound filtering. Structuralanalysis was performed as an acoustic modal analysis on therear part and the car interior with the quantitative analysis ofsport and luxury car sounds. The possibility of active noise controlwas studied and examples are given for an application ofpsychoacoustic tools for car sound quality design. Sound qualitywas obtained by an observation of certain aspects, which areempirically or theoretically connected with the design. An experimentalsound synthesis with psychometrical measuring wasapplied. The sound quality of car interior is presented takinginto consideration the criteria of objectivity, reliability and validity.